Toward New Indicators of a Journal’s Manuscript Peer Review Process - Moed, Henk F. (Frontiers in Research Metrics and Analytics, 2016)
Journal impact factor (JIF) is among the most frequently used bibliometric indicators in scientific-scholarly journal and research assessment. This paper addresses the question as to why this indicator has become so attractive and pervasive. It defends the position that the most effective way to reduce the role of citation based journal metrics in journal and research assessment is developing indicators of the quality of journals’ manuscript peer review process, based on an analysis of this process itself, as reflected in the written communication between authors, referees and journal editors in electronic submission systems This approach combines computational linguistic tools from the domain of ‘digital humanities’ with ‘classical humanistic’ text analysis and a profound knowledge of the manuscript peer review and the publication process.